2020
DOI: 10.1007/s00429-020-02146-y
|View full text |Cite
|
Sign up to set email alerts
|

GABA–glutamate supramammillary neurons control theta and gamma oscillations in the dentate gyrus during paradoxical (REM) sleep

Abstract: Several studies suggest that neurons from the lateral region of the SuM (SuML) innervating the dorsal dentate gyrus (DG) display a dual GABAergic and glutamatergic transmission and are specifically activated during paradoxical (REM) sleep (PS). The objective of the present study is to characterize the anatomical, neurochemical and electrophysiological properties of the SuML-DG projection neurons and to determine how they control DG oscillations and neuronal activation during PS and other vigilance states. For … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 60 publications
(83 reference statements)
3
25
0
Order By: Relevance
“…Most excitatory neurons in the central nervous system appear to express a vesicular transporter for the fast neurotransmitter, glutamate (vGlut1-3), but some glutamatergic neurons also express the vesicular GABA transporter vGAT, an example being a distinct group of neurons in the lateral supramammillary nucleus (SuML) (Soussi et al, 2010), an area critically involved in hippocampal theta rhythm control via direct connections with the septum and hippocampus (Borhegyi et al, 1997;Kiss et al, 2000). The net action of GABA/glutamate co-transmission from SuML to hippocampus was shown to be excitatory (Hashimotodani et al, 2018) and activation of the SuMLhippocampal axis activates dentate gyrus (DG) neurons and increases DG theta and gamma power during paradoxical sleep (Billwiller et al, 2020). The rat NI is directly and reciprocally connected with the medial and lateral parts of the SuM (Goto et al, 2001;Olucha-Bordonau et al, 2003), and similar to the SuM, theta phase-locked neurons were identified in the NI (Kirk and McNaughton, 1991;Ma et al, 2013;Li et al, 2020;Trenk et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Most excitatory neurons in the central nervous system appear to express a vesicular transporter for the fast neurotransmitter, glutamate (vGlut1-3), but some glutamatergic neurons also express the vesicular GABA transporter vGAT, an example being a distinct group of neurons in the lateral supramammillary nucleus (SuML) (Soussi et al, 2010), an area critically involved in hippocampal theta rhythm control via direct connections with the septum and hippocampus (Borhegyi et al, 1997;Kiss et al, 2000). The net action of GABA/glutamate co-transmission from SuML to hippocampus was shown to be excitatory (Hashimotodani et al, 2018) and activation of the SuMLhippocampal axis activates dentate gyrus (DG) neurons and increases DG theta and gamma power during paradoxical sleep (Billwiller et al, 2020). The rat NI is directly and reciprocally connected with the medial and lateral parts of the SuM (Goto et al, 2001;Olucha-Bordonau et al, 2003), and similar to the SuM, theta phase-locked neurons were identified in the NI (Kirk and McNaughton, 1991;Ma et al, 2013;Li et al, 2020;Trenk et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Here we showed that the same SuML neurons are reactivated one week apart during PSR while different GCs are reactivated in the DG. Using optogenetic stimulation of terminals of SuML neurons in the DG, we recently showed that all GCs are both excited and inhibited by the SuML projection 38 . It suggests that although the SuML neurons excite all GCs during PS, other input(s) like the performant path 39 is (are) likely necessary to induce the activation of different GCs over two periods of PSR separated by one week.…”
Section: Differential Activation Of the Hippocampus (Hip) During W And Psrmentioning
confidence: 99%
“…With direct connections and indirect connections via the medial septum to the hippocampus, SuM activity is involved in the hippocampal θ rhythm ( 7 , 8 ). Recent studies have indicated that the SuM projection to the DG is related to spatial memory retrieval ( 9 ), sleep and arousal ( 10 12 ), and contextual novelty ( 13 ). Despite emerging evidence that the SuM-DG pathway contributes to several brain functions, it remains unknown how the SuM afferents to the DG are involved in brain functions at the cellular, synaptic and circuit levels.…”
mentioning
confidence: 99%
“…Recent studies have revealed that the SuM neurons make monosynaptic connections to granule cells (GCs), the DG principal neurons, and corelease glutamate and GABA onto GCs ( 10 , 12 15 ). This glutamatergic and GABAergic cotransmission exerts a net excitatory effect on GCs and modulates GC firing through temporal association with entorhinal cortical inputs ( 14 , 15 ).…”
mentioning
confidence: 99%